A novel heating-assisted density separation method for extracting microplastics from sediments. (October 2020) - Zhang, Xiangnan; Yu, Kai; Zhang, Hong; Liu, Yuning; He, Jing; Liu, Xiangyu; Jiang, Jie
Abstract: Microplastics (MPs) pollution in the marine has become a global concern. To obtain accurate measurements of MPs in the marine sediments is important for understanding its effects and potential risks to the environment. In this study, we developed a novel method for extracting MPs from sediments by density flotation of sodium dihydrogen phosphate (NaH2 PO4 ) solution, which utilized the heating-assisted to increase the density of separation solution. It features high density, nontoxic, and economic, indicating its promising application in the MPs extraction. A standard procedure based on NaH2 PO4 for extracting MPs from sediments was established and validated by the recovery experiments of seven common plastics. Results showed NaH2 PO4 solution exhibited higher recovery rates than the commonly-used NaCl solution; three plastics with high density couldn't be recovered by NaCl, while NaH2 PO4 was available for all the studied MPs. A large number of real beach samples was collected and validated by this method, and the abundance and characteristic of the collected MPs were further analyzed. Results exhibited the heating-assisted NaH2 PO4 could be a promising way for extracting MPs in environmental samples. Highlights: NaH2 PO4 has a higher recovery than NaCl in extracting MPs from sediments. The heating-assisted can be used to increase the density of separation solutions. NaH2 PO4 features high density, non-toxicity, and low-cost. MP pollution of a Weihai beach was investigated by this method.